CHARACTERISTICS OF LOW CARBON STEEL AND HIGH STRENGTH LOW ALLOY AT HIGH STRAIN RATE AS CRASHWORTHINESS DATA ANALYSIS - PHILO WARDANI, IFTIKA
For conducting crashworthiness simulation using Indonesian material, then author conducted researched for analysis characteristic material during impact loaded with SS400, API-5L, and S355JR as selected material. SS400 is widely used as structural material for wagon, API5L was proposed for impact absorbing material. While material S355JR, which equivalent to SM490, was used for making bogie and centersill. Testing was performed using the Split Hopkinson Pressure Bar, with a strain rate from 102 up to 103 /s. This tested used for analizing material behaviour under high strain rate. From the results that obtained, material SS400 has the highest yield stress and flow stress comparing with API5L and S355JR. From the test results also known that SS400 material can absorb the highest energy. In addition, this research also obtained curve fitting parameter using Simplified Johnson-Cook method. From this curve fitting we get Johnson Cook equation for SS400 material is 478.67396,54 ,10,032 , for material API5L is 387,94304,87 ,10,035 , and for S355JR is 386,70403,75 ,10,033 . From the Johnson Cook parameter that obtained is also known that the material SS400 has the lowest strain rate hardening dependable.